2012
DOI: 10.1590/s1415-65552012000100004
|View full text |Cite
|
Sign up to set email alerts
|

Evolução de conhecimentos no relacionamento comprador-fornecedor

Abstract: A partir de uma perspectiva dinâmica, este trabalho tem como objetivo avaliar como o relacionamento comprador-fornecedor influencia a evolução de conhecimentos tecnológicos, de mercado e logística, de processo e relacional, dominados por ambos os atores. Para tanto, foi feito um estudo de caso de natureza qualitativa e perspectiva longitudinal de um relacionamento entre duas firmas industriais. Embasado por dados coletados a partir de múltiplas fontes de dados, chegou-se ao resultado de que a transferência e/o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
1
2
0
Order By: Relevance
“…Zeta demonstrated that they maintain partnerships and learning relationships, but not reliability, since dealing with patent development involves suspicion as to the level of trust that must be maintained with the agents with whom they communicate. These findings correspond to reports by Rezende, Lima and Versiani (2012), who claim that relationships are the basis for the acquisition of all forms of knowledge.…”
Section: Presentation and Discussion Of Cases And Resultssupporting
confidence: 91%
“…Zeta demonstrated that they maintain partnerships and learning relationships, but not reliability, since dealing with patent development involves suspicion as to the level of trust that must be maintained with the agents with whom they communicate. These findings correspond to reports by Rezende, Lima and Versiani (2012), who claim that relationships are the basis for the acquisition of all forms of knowledge.…”
Section: Presentation and Discussion Of Cases And Resultssupporting
confidence: 91%
“…On the other hand, part of the value comes over the time the relationship lasts and indicates the evolution of the buyer-supplier relationship, which ends up transcending the simple exchange of goods (Kumar, Banerjee, Meena, & Ganguly, 2016;Rezende, Lima, & Versiani, 2012). The benefits generated are the result of the synergies identified by the parties that lead to the efforts they make to stay in the relationship (Mena, Humphries, & Choi, 2013).…”
Section: Value-creation In Relationshipsmentioning
confidence: 99%
“…In the Brazilian automobile industry, the links between automakers and first tier suppliers are being strengthened, with the objective of obtaining greater coordination in the execution of activities and better access to external resources, for the generation of innovation, increase of productivity and reinforce the competitive capacity (Martins, Souza Filho & Pereira, 2012). Rezende, Lima and Versiani (2012) have shown that the existence of knowledge transfer between buyers (automakers) and suppliers, whether technological, market and logistics, of process or relational, depends on the type of the analyzed knowledge. So, the dependence of a supplier on a specific automaker reinforces the strategic alignment in this supply chain (Martins, Souza Filho, & Pereira, 2012).…”
Section: The Phase Of Management and Adaptation Of Dynamic Capabilitiesmentioning
confidence: 99%